Characterization of Kowoe snail and its antioxidant activity - Haslianti Haslianti; Mita Gabriella Inthe; Ermayanti Ishak (Jurnal Pengolahan Hasil Perikanan Indonesia, 2017)
Gold snail is called “Kowoe” in Celebes Island. They are  widely utilized by people as food.  This snail also has many properties and benefits.  The aims of this study were to determine the best solvent to extract the bioactive components of snails and measure the antioxidant activity. The  proximate analysis was caried out, then quantitative test of antioxidant activity by DPPH method was measured. The results of morphometric measurements showed the meat yield  11.86%. The  proximate analysis of fresh meat  consisted of water content 65.79%, 18.14% protein, 10.49% ash, 4.14% carbohydrates, and fats 3.44%, while the moisture content of dried meat contained  40/ 04%, 38.06% protein, carbohydrates 10.66%, ash 8.53% and 2.70% fat, respectively. The yield of extraction of the active compound using chloroform (non-polar) was 1.78%, ethyl acetate (semi-polar) was 3.41% and 6.63% methanol (polar).  The  snails kowoe contain more the polar of active compounds. The antioxidant activity of crude extract in methanol solvent (polar) had IC50 values  111.28 ppm (moderate).